Ginkgo biloba and Its Constituent 6-hydroxykynurenic-acid as well as Its Proanthocyanidins Exert Neurorestorative Effects against Cerebral Ischemia - Yao, Jianbiao; Qiao, Hongxiang; Jin, Zhuming; Wang, Ruwei; Huang, Haibo; Fang, Ling; Chen, Yan; Tai, Khalid; Chen, Yan; Doeppner, Thorsten Roland; Chen, Zhong; Kuchta, Kenny (Planta Medica, 2020)
Neuroprotective effects against cerebral ischemia/reperfusion (I/R) injury by Ginkgo biloba leaves are commonly attributed to the antioxidant activity of its proanthocyanidins. Furthermore, preliminary experiments identified 6-hydroxykynurenic acid (6-HKA) as a major contributor to this effect of extract of G. biloba leaves (EGb) prepared according to the Chinese Pharmacopoeia (ChP). In order to elucidate the specific contribution of both proanthocyanidins and 6-HKA to the overall neurorestorative effects of this extract according to ChP, EGb ChP was separated into pure 6-HKA and a newly developed Ginkgo proanthocyanidin extract (GPE), enriched in proanthocyanidins but not containing 6-HKA. Male Sprague-Dawley rats were divided into the groups: sham: 8; model (placebo): 25; GPE 80 mg/kg: 13; GPE 40 mg/kg: 13; GPE 20 mg/kg: 16; grape seed extract (negative control) 40 mg/kg: 18; nimodipine (positive control) 2 mg/kg: 8. All non-sham animals were subjected to cerebral I/R injury by occluding the middle cerebral artery with a nylon suture that was removed after 2 h of ischemia to establish reperfusion. For comparison, a parallel series of experiments were performed with 6-HKA. In these in vivo experiments, neurological dysfunctions were reduced by both GPE and 6-HKA, and both average infarct size and concentrations of malondialdehyde (MDA) and super oxide dismutase (SOD) were significantly ameliorated as compared to the model group. This data, therefore, demonstrates that the neuroprotective effects of EGb cannot be explained by a purely chemical antioxidative effect alone as has been previously proposed, especially with regards to the proanthocyanidins. A pharmacological neurorestorative effect of EGb on neurons and brain tissue itself seems to be a much more straightforward explanation for the presented observations. This effect is most likely explained by the synergistic action of both its numerous phenolic constituents (GPE) and 6-hydroxykynurenic acid (6-HKA), which could be identified as one major contributor to the observed activity.
Keywords: Ginkgo biloba; Ginkgoaceae; cerebral ischemia; proanthocyanidins; 6-hydroxykynurenic acid (6-HKA); neuroprotection